Gratitude as a Moral Value: A Corpus-based Analysis of its Representation in the Lexis of Malay Primary School Textbooks (Malaysian Journal of Learning and Instruction, 2004)
This paper reports on a study of the representation of a moral value, gratitude, in the lexis of Bahasa Malaysia primary school textbooks, Years One to Six. The study was based on the assumption that repeated occurrences of these representations over the years of schooling could contribute to the social learning, among children, of patterns and contexts for the expression of this value. A corpus of Bahasa Malaysia subject textbooks was analysed to seek consistent portrayals of gratitude via frequencies of occurrence, sentential contexts as well as collocation. Patterns in representation are discussed at lexical level. TERIMA KASIH was the most frequently occurring lemma for the expression of this value. It was found that the child was more often represented as an expresser of thanks, but less as a receive,: There were limited occurrences of expressions of gratitude between child peers. Gratitude also tended to be represented in the form of formulaic expressions, and in the context of public announcements rather than personal gestures. Some limitations of the corpus-based approach used are discussed.